2022
DOI: 10.21775/cimb.042.145
|View full text |Cite
|
Sign up to set email alerts
|

Immune Response to Borrelia: Lessons from Lyme Disease Spirochetes

Abstract: The mammalian host responds to infection with Borrelia spirochetes through a highly orchestrated immune defense involving innate and adaptive effector functions aimed toward limiting pathogen burdens, minimizing tissue injury, and preventing subsequent reinfection. The evolutionary adaptation of Borrelia spirochetes to their reservoir mammalian hosts may allow for its persistence despite this immune defense. This review summarizes our current understanding of the host immune response to B. burgdorferi sensu la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
38
0
7

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(47 citation statements)
references
References 403 publications
(560 reference statements)
2
38
0
7
Order By: Relevance
“…Borrelia burgdorferi establishes persistent and non-resolving infections in fully immunocompetent mice, strongly suggesting that the bacteria have developed multiple and likely complex immune evasion strategies (9,11). Both innate and adaptive immune responses control B. burgdorferi in these hosts [reviewed in (12)]. These species rarely, and only transiently, develop clinical manifestations of disease, without an obvious correlation between the tissue-loads of B. burgdorferi and clinical manifestations, except in severely immunocompromised mice, for example those that lack T and B cells (SCID mice), or the ability to activate innate immune effectors because of deletions in the toll-like receptor (TLR) 2 or TLR adaptor protein MyD88 (13)(14)(15).…”
Section: Role Of the Immune System In Response To B Burgdorferi Infectionmentioning
confidence: 99%
See 3 more Smart Citations
“…Borrelia burgdorferi establishes persistent and non-resolving infections in fully immunocompetent mice, strongly suggesting that the bacteria have developed multiple and likely complex immune evasion strategies (9,11). Both innate and adaptive immune responses control B. burgdorferi in these hosts [reviewed in (12)]. These species rarely, and only transiently, develop clinical manifestations of disease, without an obvious correlation between the tissue-loads of B. burgdorferi and clinical manifestations, except in severely immunocompromised mice, for example those that lack T and B cells (SCID mice), or the ability to activate innate immune effectors because of deletions in the toll-like receptor (TLR) 2 or TLR adaptor protein MyD88 (13)(14)(15).…”
Section: Role Of the Immune System In Response To B Burgdorferi Infectionmentioning
confidence: 99%
“…This movement can be tracked in real time in mice with the use of multiphoton/confocal microscopy and fluorescently labeled B. burgdorferi . Ongoing imaging analysis revealed that the number of spirochetes peaked around 7–10 days after infection ( 12 ). This peak was followed by a dramatic drop in spirochete numbers, where they persisted for the duration of the experiment.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Borreliella spirochetes are widely held to be extracellular pathogens for which phagocytes, antibody and complement are critical for host defense (4). Bb-specific antibodies prevent infection in both animal models and humans and contribute to a reduction in pathogen burden and resolution of disease manifestations in mouse models (4). In humans, a robust circulating plasmablast response was found to correlate with more rapid resolution of LD symptoms after antibiotic treatment for EM (5).…”
Section: Introductionmentioning
confidence: 99%